E-241 Independent validation of the efficacy and safety of transvenous embolization of csf-venous fistula. (23rd July 2022) - Parizadeh, D; Fermo, O; Miller, D; Gupta, V; Vibhute, P; Rozen, T; Huynh, T
Abstract : Introduction: Endovascular transvenous embolization is a novel treatment for patients with spontaneous intracranial hypotension (SIH) secondary to CSF-venous fistulas (CVF)(1). The technique was introduced recently at a single center with promising results. 1 We sought to perform the first independent validation of the efficacy and safety of this novel procedure. Methods: Data were collected prospectively: Inclusion criteria were: 1) clinical diagnosis of SIH, 2) definitive diagnosis of CVF on either digital subtraction myelogram or CT myelogram, 3) transvenous embolization for treatment of CVF at our institution between December 2020 - March 2022. Clinical symptoms pre and post-embolization were assessed using standardized scores including the Headache Impact Test (Hit-6) 2 and Patient Global Impression of Change (PGIC) 3 score. Features of SIH pre and post-embolization were assessed using the Bern SIH score 4 on brain MRI. Procedural and post-procedural complications were recorded. Pre-and post-embolization outcomes were compared with Wilcoxon Signed Rank test. Results: Eighteen patients (mean [SD] age 58 [10] years, 78% female) underwent transvenous embolization for treatment of CVF. Median (IQR) follow-up was 3.5(4.5) months for clinical (available for 17 patients) and 2 (8) months for imaging outcomes, available for 17 and 11 patients, respectively. Among 17 patients with available clinical follow-up, headache severity decreased significantly post-embolization (mean HIT-6 score of 63.1 pre-embolization and 38.2 post-embolization, p = 0.001) and 94% reported 'very much improved' on PGIC (score of 1). Of 11 patients with available follow-up imaging, post-operative Bern score significantly decreased(mean Bern score of 7.5 vs 3.1, p = 0.009). One case did not improve in clinical or imaging findings. There were no neurological/hemorrhagic complications. Side effects were localized back pain (50%) and rebound headache (55%) which resolved within one month with medical treatment in all cases. Conclusion: Transvenous embolization is a highly efficacious and safe treatment for CVF in patients with SIH. References: Brinjikji W, Garza I, Whealy M, et al . Clinical and imaging outcomes of cerebrospinal fluid-venous fistula embolization. Journal of NeuroInterventional Surgery. Kosinski M, Bayliss MS, Bjorner JB, et al . A six-item short-form survey for measuring headache impact: the HIT-6. Qual Life Res 2003;12:963–74. Dworkin RH, Turk DC, Farrar JT, et al . Core outcome measures for chronic pain clinical trials: IMMPACT recommendations. Pain 2005;113:9–19. Dobrocky T, Grunder L, Breiding PS, et al . Assessing spinal cerebrospinal fluid leaks in spontaneous intracranial hypotension with a scoring system based on brain magnetic resonance imaging findings. JAMA Neurol 2019;76:580. Disclosures: D. Parizadeh: None. O. Fermo: None. D. Miller: None. V. Gupta: None. P. Vibhute: None. T. Rozen: None. T. Huynh: None.